2022 IEEE Conference on Control Technology and Applications (CCTA) 2022
DOI: 10.1109/ccta49430.2022.9966102
|View full text |Cite
|
Sign up to set email alerts
|

MPC for Propofol Anesthesia: the Noise Issue

Abstract: The design of automatic control systems for general anesthesia is a challenging task due to the severe safety requirements and process constraints. This is even more complex when model-based control techniques are used due to the significant variability of the process model. Additionally, issues like noisy measurements and interference also influence the control system overall performance. In this context, adequate filtering and control system sampling period selection should be analyzed to test their influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The effect of noise is also considered. The noise signal already employed in [22], which has been extracted from real clinical data, is added to the BIS. The noise and disturbance signals are shown in Figure 5.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of noise is also considered. The noise signal already employed in [22], which has been extracted from real clinical data, is added to the BIS. The noise and disturbance signals are shown in Figure 5.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Then, T max has been set to 10 seconds (that is, n=10) because of safety reasons, as this ensures the minimal performance of the closed-loop control system [11]. Indeed, in a previous work [22], it was shown that the sampling period of 10 second is the maximum value that allows the clinical requirements to be met in terms of accuracy and disturbance compensation capability in the presence of measurement noise. Additionally, the value of β has been fixed to 5.…”
Section: Control System Tuningmentioning
confidence: 99%
See 3 more Smart Citations